2010
DOI: 10.1007/s10750-010-0395-4
|View full text |Cite
|
Sign up to set email alerts
|

Induced defences in marine and freshwater phytoplankton: a review

Abstract: Many organisms have developed defences to avoid predation by species at higher trophic levels. The capability of primary producers to defend themselves against herbivores affects their own survival, can modulate the strength of trophic cascades and changes rates of competitive exclusion in aquatic communities. Algal species are highly flexible in their morphology, growth form, biochemical composition and production of toxic and deterrent compounds. Several of these variable traits in phytoplankton have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(150 citation statements)
references
References 110 publications
3
145
0
2
Order By: Relevance
“…Similarly, Lürling (1998) observed that only exudates from Daphnia grazing on digestible food induced colony formation in S. acutus. Cues related to active feeding may thus be the most reliable indication of the risk of herbivory for phytoplankton (Van Donk et al, 2011), explaining why cues from actively grazing consumers may produce a stronger induction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Lürling (1998) observed that only exudates from Daphnia grazing on digestible food induced colony formation in S. acutus. Cues related to active feeding may thus be the most reliable indication of the risk of herbivory for phytoplankton (Van Donk et al, 2011), explaining why cues from actively grazing consumers may produce a stronger induction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential cues released by the grazers, mechanical damage of the algae may signal the risk of grazing, especially when feeding is "sloppy", even if the message may not always be reliable since algae also lyse, e.g. due to attack by viruses (Van Donk et al, 2011). The effect of mechanical damage on the potential inducible defenses in phytoplankton has been rarely studied (reviewed in Van Donk et al, 2011;see Lampert et al, 1994;Lürling, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrusek et al, 2009). The seasonal cyclomorphosis in rotifers and cladocerans (Dodson, 1989) or the production of spines in phytoplankton (Van Donk et al, 2011) is commonly observed effect of inducible defences. Predators thus (i) select those organisms which have defensive phenotypes and (ii) alter their traits in different environments (Werner & Peacor, 2003), therefore decreasing the colonization success of those organisms with phenotypes more susceptible to predation 123 (Covich, 2010).…”
Section: Biological Filters and Reproductive Strategiesmentioning
confidence: 99%